A identidade do rock e seus subgêneros no contexto da moda contemporânea - Ruella, Larissa Furtado (2015)
The rock is one of the greatest musical genres that emerged with the purpose of rebellion. Since its inception has revolutionized and renewing each year with new styles and so branching. To identify with social protest movements, the rock has marked the society through the decad457es allowing young propagate his ideals. The rock is combined with fashion it is for her that he expresses his attitude and identity. Each year since its inception have been showing new ways to express themselves, to dress and behave through music marking each decade for a specific style of dress. In this sense this study aims to address the rock in the context of contemporary fashion, its subgenres and influences in a chronological analysis to create a homogeneous brand with influences in various subgenres of rock'n'roll.